RENEWABLE ENERGY AND ATMOSPHERIC POLLUTION - MRACNA, Viliam (Trends in education, 2010)
The contribution deals with coping with the consequences of possible climate change. Environmental Technology study programme focuses on the greening of industrial production and the familiarity of the issue of environmental impact and reducing the impact.
Keywords: Greenhouse gases; environment; global warming.